1998
DOI: 10.1002/cc.10203
|View full text |Cite
|
Sign up to set email alerts
|

Shared Governance in California

Abstract: The 1988 introduction of shared governance into California–s community colleges did not ultimately materialize into an anticipated model of collegiality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interpretations of legislation and government policy give rise to particular institutional behaviors. In California interpretations by numerous college faculty and administrators suggested that institutional governance was "shared" or jointly carried out by faculty and administrators (White, 1998). Governance in California community colleges was viewed as shared governance, even though Assembly Bill 1725 never used the word shared, indicating instead that faculty were participants in governance (Levin, 2000).…”
Section: Implications For Practitionersmentioning
confidence: 98%
See 1 more Smart Citation
“…Interpretations of legislation and government policy give rise to particular institutional behaviors. In California interpretations by numerous college faculty and administrators suggested that institutional governance was "shared" or jointly carried out by faculty and administrators (White, 1998). Governance in California community colleges was viewed as shared governance, even though Assembly Bill 1725 never used the word shared, indicating instead that faculty were participants in governance (Levin, 2000).…”
Section: Implications For Practitionersmentioning
confidence: 98%
“…The California community college governance story begins with Assembly Bill 1725 (1988), an omnibus bill that reputedly changed California community colleges by eroding the authority of college administrators and elevating faculty (White, 1998). The critical language for faculty elevation in governance appears in section 70902, article 7, which compels the governing board to establish procedures "to ensure faculty, staff, and students the opportunity to express their opinions at the campus level and to ensure that these opinions are given every reasonable consideration, and the right to participate effectively in district and college governance, and the right of academic senates to assume primary responsibility for making recommendations in the areas of curriculum and academic standards."…”
Section: Participation Broadly Defined: the Academic Senate In Califomentioning
confidence: 99%